Analysis of the Potential and Challenges of Ecotourism in Supporting Physical Environmnetal Aspects in Tangkahan - Ikhlas Ramadhan; Andrea Naomi Siahaan; Muhammad Zidan; Raihanah Annisa (Politeknik Sahid, 2026)
This research aims to analyze the potential and challenges of ecotourism development in supporting the preservation of physical environmental aspects in the Tangkahan area, Langkat Regency, North Sumatra. The physical environment, such as soil quality, water, vegetation, and natural landscape is the main assets that support the attractiveness of ecotourism. This uses a qualitative descriptive approach through direct observation and semi-structured interviews involving local managers, tourists, and related organizations. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The research results showed that Tangkahan has great potential as a conservation-based ecotourism destination, with preserved water and air quality and high biodiversity. However, there are significant challenges such as limited infrastructure, low promotion, and environmental threats due to uncontrolled tourism activities. The implications of this study emphasize the importance of an integrated management strategy involving local communities, improved supporting facilities, and environmental education for tourists to ensure the area's sustainability. These findings can be the basis for formulating ecotourism development policies based on physical environment conservation.